Bone formation in sinus augmentation procedures using autologous bone, porcine bone, and a 50 : 50 mixture: a human clinical and histological evaluation at 2 months. Issue 10 (26th May 2014) - Cassetta, Michele; Perrotti, Vittoria; Calasso, Sabrina; Piattelli, Adriano; Sinjari, Bruna; Iezzi, Giovanna
Abstract Objectives The aim of this study was to perform a 2 months clinical and histological comparison of autologous bone, porcine bone, and a 50 : 50 mixture in maxillary sinus augmentation procedures. Materials and methods A total of 10 consecutive patients, undergoing two‐stage sinus augmentation procedures using 100% autologous bone (Group A), 100% porcine bone (Group B), and a 50 : 50 mixture of autologous and porcine bone (Group C) were included in this study. After a 2‐month healing period, at the time of implant insertion, clinical evaluation was performed and bone core biopsies were harvested and processed for histological analysis. Results The postoperative healing was uneventful regardless of the materials used for the sinus augmentation procedures. The histomorphometrical analysis revealed comparable percentages of newly formed bone, marrow spaces, and residual grafted material in the three groups. Conclusion The clinical and histological results of this study indicated that porcine bone alone or in combination with autologous bone are biocompatible and osteoconductive materials and can be successfully used in sinus augmentation procedures.